Empowering Teachers through the Development of Articulate Storyline-Based Digital Learning Media on Climate Change Education - Putri, Elyana; Rofiah, Nurul Hidayati (OJS Universitas Muhammadiyah Gresik, 2025)
Climate change is a vital topic in elementary science education, yet it remains challenging for students to grasp due to its abstract nature. At the same time, many teachers face limitations in developing digital-based instructional media. This study aimed to create interactive learning media using Articulate Storyline for fourth-grade students and to empower teachers by involving them in both the development and implementation processes. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Field testing with 21 students showed a notable improvement in learning outcomes, with average pre-test and post-test scores of 51.66 and 86.38, respectively. The N-Gain score of 0.70 indicates that the media was effective in enhancing student understanding. Moreover, teacher participation in the development process contributed to improved digital literacy and pedagogical skills, especially in integrating technology into classroom instruction. The Articulate Storyline-based media proved to be both practical and effective for elementary science learning, supporting the goals of the Merdeka Curriculum, which emphasizes differentiated instruction and the integration of educational technology.